Reviews: Catalogue of Ceutorhynchinae of the World, with a key to Genera, The Geometrid Moths of Europe, Die Larven der Europäeischen Noctuidae - Silfverberg, Hans; Tammaru, Toomas; Itämies, Juhani (Entomologica Fennica, 2005)
Colonnelli, E. 2004: Catalogue of Ceutorhynchinae of the World, with a key to Genera. – Argania Editio, Barcelona. 124 pp. ISBN 84- 931847-6-4. Price 80 EUR. Hausmann, A. 2004: The Geometrid Moths of Europe, Vol. 2: Sterrhinae. Apollo Books, Kirkeby Sand 19, DK-5771 Stenstrup, Denmark. ISBN 87-88757-37-4, Hardback, 600 pp. Price 960,00 DKK. Beck, H. 1999–2000: Die Larven der Europäeischen Noctuidae. Revision der Systematik der Noctuidae (Larvae of European Noctuidae. Revision of the systematics of the Noctuidae). With the help of Matti Ahola (numerous drawings) and Ivar Hasenfuss (systematic notes on Noctuoidea, Acronictinae, and occasional drawings). Volumes I–IV. 864+448+336+512 pp. ISSN 0723-595X, ISBN 3-923807-04-X. Price 530 EUR.